The effectiveness of tablet-based application as a medium of feedback in performance analysis during a competitive match in elite soccer - Mohamad Razali, Abdullah; Norzulaika, Alias; Vijayamurugan, Eswaramoorthi; Rabiu Muazu, Musa; Ahmad Bisyri Husin, Musawi Maliki (2017)
This study aims to examine the effectiveness of Tablet based application (TBA) as a medium for feedback in real time at a half-time interval of a competitive match in improving the performance of soccer players. StatWatch application was installed on a tablet phone and used as a device for data collection. Eleven performance analysts were recruited to assist in the data collection such that each performance analysts covered a particular player during the game. Players Performances were assessed based on clearing, crossing, dribbling, heading, pursuing the loose ball, shooting, foul and through pass. Data were collected as the game progressed, and information was transmitted to the controller of the analysis before being relayed to the chief coach at the half time interval of every match. Matches of the club for eight weeks were analysed. One-way repeated measure ANOVA was used to assess the progress of the team in between the first and second halves of the matches played. The result shows improvement on the performances of the club at the second halves of the eight matches played (F (1, 14.10) = 8.94, p < .05). A follow-up test demonstrates a significant progress on the overall team performance from week1 to week 8, p > 0.001. TBA appeared to be a useful medium for providing feedback at a first half interval of a competitive match to improving the performance of soccer players during the subsequent period.